(untitled) (Международный научный журнал «Инженер», 2026)
The article explores the prospects of using new materials for the production of friction wedges in vibration dampers for freight car bogies, taking into account the design requirements. Research has been conducted on reducing harmful impurities in the composition of cast iron and improving its strength characteristics. The article considers various options for the mass fraction of elements in the cast iron composition, depending on the type of cast iron, and provides approximate data on hardness (HV) on the walls of castings with different cross-sections. The reliability of the friction wedge vibration damper (FWVD) has a significant impact on the service life of rolling stock, as the friction force created to dampen vertical and horizontal oscillations of the wagon body decreases over time due to the wear of the working surfaces of the friction wedge. The friction wedge is a rapidly wearing component: the average mileage of grey cast iron friction wedges before replacement is about 100,000 kilometers. The annual demand for FWVDs, solely for depot repairs, exceeds 100,000 units. During the wear process, approximately 0.3 thousand tons of cast iron are irreversibly lost. Key research areas include optimizing the chemical composition, enhancing the physicomechanical and tribological properties, as well as mathematical modeling of FWVD performance under various operating conditions and predicting their behavior in service.